Measurement of the inclusive cross-sections of single top-quark and top-antiquark t-channel production in pp collisions at s√ = 13 TeV with the ATLAS detector - Aaboud, M. (2017)
A measurement of the t-channel single-top-quark and single-top-antiquark production cross- sections in the lepton+jets channel is presented, using 3.2 fb −1 of proton?proton collision data at a centre-of-mass energy of 13 TeV, recorded with the ATLAS detector at the LHC in 2015. Events are selected by requiring one charged lepton (electron or muon), missing trans- verse momentum, and two jets with high transverse momentum, exactly one of which is re- quired to be b-tagged. Using a binned maximum-likelihood fit to the discriminant distribution of a neural network, the cross-sections are determined to be σ(tq) = 156±5 (stat.)±27 (syst.)± 3 (lumi.) pb for single top-quark production and σ( t  ̄ q) = 91±4 (stat.)±18 (syst.)±2 (lumi.) pb for single top-antiquark production, assuming a top-quark mass of 172.5 GeV. The cross- section ratio is measured to be R t = σ(tq)/σ( t  ̄ q) = 1.72 ± 0.09 (stat.) ± 0.18 (syst.). All results are in agreement with Standard Model predictions.